Reduction of Nitrous Oxide by Light Alcohols Catalysed by a Low‐Valent Ruthenium Diazadiene Complex. Issue 20 (6th March 2023) - Bösken, Jonas; Rodríguez‐Lugo, Rafael E.; Nappen, Sven; Trincado, Monica; Grützmacher, Hansjörg
Abstract: Decomposition of the environmentally harmful gas nitrous oxide (N2 O) is usually performed thermally or catalytically. Selective catalytic reduction (SCR) is currently the most promising technology for N2 O mitigation, a multicomponent heterogeneous catalytic system that employs reducing agents such as ammonia, hydrogen, hydrocarbons, or a combination thereof. This study reports the first homogenous catalyst that performs the reduction of nitrous oxide employing readily available and cheap light alcohols such as methanol, ethanol or ethylene glycol derivatives. During the reaction, these alcohols are transformed in a dehydrogenative coupling reaction to carboxylate derivatives, while N2 O is converted to N2 and H2 O, later entering the reaction as substrate. The reaction is catalysed by the low‐valent dinuclear ruthenium complex [Ru2 H(μ‐H)(Me2 dad)(dbcot)2 ] that carries a diazabutadiene, Me2 dad, and two rigid dienes, dbcot, as ligands. The reduction of nitrous oxide proceeds with low catalyst loadings under relatively mild conditions (65–80 °C, 1.4 bar N2 O) achieving turnover numbers of up to 480 and turnover frequencies of up to 56 h −1 . Abstract : A low valent diruthenium dihydride complex catalyses the reduction of nitrous oxide with primary alcohols or hydrogen. Light alcohols (methanol, ethanol) or benzylic alcohols are transformed in a dehydrogenative coupling reaction to carboxylate derivatives, while N2 O is converted to N2 and H2 O.The reaction proceeds under mild conditions achieving TON of up to 480 and TOF of 56 h −1 .